SUMO1 regulates post-infarct cardiac repair based on cellular heterogeneity - Zhihao Liu; Xiaozhi Liu; Li Liu; Ying Wang; Jie Zheng; Lan Li; Sheng Li; Han Zhang; Jingyu Ni; Chuanrui Ma; Xiumei Gao; Xiyun Bian; et al. (Elsevier, 2023)
Small ubiquitin-related modifier (SUMOylation) is a dynamic post-translational modification that maintains cardiac function and can protect against a hypertrophic response to cardiac pressure overload. However, the function of SUMOylation after myocardial infarction (MI) and the molecular details of heart cell responses to SUMO1 deficiency have not been determined. In this study, we demonstrated that SUMO1 protein was inconsistently abundant in different cell types and heart regions after MI. However, SUMO1 knockout significantly exacerbated systolic dysfunction and infarct size after myocardial injury. Single-nucleus RNA sequencing revealed the differential role of SUMO1 in regulating heart cells. Among cardiomyocytes, SUMO1 deletion increased the Nppa+ Nppb+ Ankrd1+ cardiomyocyte subcluster proportion after MI. In addition, the conversion of fibroblasts to myofibroblasts subclusters was inhibited in SUMO1 knockout mice. Importantly, SUMO1 loss promoted proliferation of endothelial cell subsets with the ability to reconstitute neovascularization and expressed angiogenesis-related genes. Computational analysis of ligand/receptor interactions suggested putative pathways that mediate cardiomyocytes to endothelial cell communication in the myocardium. Mice preinjected with cardiomyocyte-specific AAV-SUMO1, but not the endothelial cell-specific form, and exhibited ameliorated cardiac remodeling following MI. Collectively, our results identified the role of SUMO1 in cardiomyocytes, fibroblasts, and endothelial cells after MI. These findings provide new insights into SUMO1 involvement in the pathogenesis of MI and reveal novel therapeutic targets.